The marketability of bank assets and managerial rents: implications for financial stability - Falko Fecht; Wolf Wagner (Deutsche Bundesbank, 2007)
Ongoing financial innovation and greater information availability increase the tradability of bank assets and reduce banks' dependence on individual bank managers as private information in the lending process declines. In this paper we argue that this has two effects on banks, with opposing implications for banking stability. First, the hold-up problem between bank managers and shareholders becomes less severe. Consequently, banks' capital structure needs to be less concerned with disciplining the management. Deposits -the most effective disciplining device- can be reduced, increasing banks' resilience to adverse return shocks. However, limiting the hold-up problem also diminishes bank managers' rents, reducing their incentives to properly monitor and screen borrowers, with adverse implications for asset quality. Thus, even though the improved marketability of bank assets allows banks to adopt a safer capital structure, the default risk of banks does not necessarily decline.
Keywords: G32; G21; G28; 330; Marketability; Incentives; Financial Innovations; Financial Stability; Bank; Bankmanager; Corporate Governance; Agency Theory; Leistungsorientierte Vergütung; Kreditgeschäft; Finanzinnovation; Finanzderivat; Securitization; Moral Hazard; Bankenkrise; Finanzmarktkrise; Theorie